2021
DOI: 10.9767/bcrec.16.2.10505.366-373
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous Magnesium Oxide Adsorbent Prepared via Lime (Citrus aurantifolia) Peel Bio-templating for CO2 Capture

Abstract: The utilization of the lime (Citrus aurantifolia) peel as a template can improve the adsorbent’s structural properties, which consequently affect its CO2 uptake capacity. Herein, a mesoporous magnesium oxide (MgO-lime (Citrus aurantifolia) peel template (LPT)) adsorbent was synthesized using an LPT. MgO-LPT demonstrated improved structural properties and excellent CO2 uptake capacity. Moreover, another MgO adsorbent was prepared via thermal decomposition (MgO-TD) for comparison. The prepared adsorbents were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This study showed a promising application of filter paper templating in tuning the physicochemical features of MgO. Additionally, in another study, the diverse selection of the magnesium precursor and preparation growth medium has been reported successfully influence the morphological development of the MgO, that tuned its physicochemical properties, particularly magnesium nitrate (precursor) and ethylene glycol (growth medium) [9,12,10]. With the magnesium nitrate and ethylene glycol utilisation together with filter paper usage as templating material, it is expected to influence the improvement of the MgO adsorption performance.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…This study showed a promising application of filter paper templating in tuning the physicochemical features of MgO. Additionally, in another study, the diverse selection of the magnesium precursor and preparation growth medium has been reported successfully influence the morphological development of the MgO, that tuned its physicochemical properties, particularly magnesium nitrate (precursor) and ethylene glycol (growth medium) [9,12,10]. With the magnesium nitrate and ethylene glycol utilisation together with filter paper usage as templating material, it is expected to influence the improvement of the MgO adsorption performance.…”
Section: Introductionmentioning
confidence: 63%
“…For the MgO solely, the alteration of the physicochemical features has been documented as achievable through the fabrication of MgO using an appropriate preparation method. As reported in previous studies, the conventional thermal degradation method has been reported to exhibit MgO with densely aggregated spherical-shaped morphological features with 1.65 μm particle size (average) [12,10]. With these morphological features, the MgO displayed a significantly low surface area of less than 15 m 2 /g, which could be considered as undesired structural feature in accomplishing high adsorption performance of the adsorbent.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations